Những dấu hiệu về tướng Granulit trong đới Sông Hồng - Thắng, Trần Tất; Anh, Trần Tuấn (Vietnam Journal of Earth Sciences, 2000)
New mineralogical evidence of granulite facgs in Red Rive’s metamorphic belt